Penyisihan COD dan TSS pada Limbah Cair Industri Tahu dengan Kombinasi Metode Elektrokoagulasi dan Filtrasi Menggunakan Media Biji Asam Jawa (Tamarindus indica L) - Damajanti, Neni; Ubaidillah, Saad (Proceedings Series on Physical & Formal Sciences, 2023)
This study aimed to treat tofu wastewater using electrocoagulation and filtration methods with tamarind seed media. This study was conducted on a lab scale with a capacity of 2 liters, using Al-Al electrodes with a voltage of 13 volts. The variables studied were EC time (20, 30, 40, 50, and 60 minutes) and electrode plate area (90 cm2 and 99 cm2) with a thickness of 1 mm. The parameters measured were COD and TSS of tofu wastewater before and after treatment. The results showed that the electrocoagulation and filtration methods with tamarind seed media could reduce the COD and TSS levels of tofu wastewater significantly. The optimal condition was achieved at EC time of 50 minutes and plate area of 99 cm2, with COD removal of 78.7% and TSS removal of 88%. This was due to the production of metal ions (Al3+) as destabilizing agents at the anode, the formation of flocs by protein and tannin in tamarind seeds, and the pH reduction by ascorbic acid and citric acid in tamarind seeds. This method had the advantage of not using synthetic chemicals and producing a more environmentally friendly final product.